2015
DOI: 10.1007/s00221-015-4335-4
|View full text |Cite|
|
Sign up to set email alerts
|

Hazard levels of warning signal words modulate the inhibition of return effect: evidence from the event-related potential P300

Abstract: Warning signal words are often used to convey valuable information about potential dangers in everyday life. In this study, we explored whether and how the hazard level of warning signal words modulated participants' attention to subsequent targets. Event-related potentials with high temporal resolution were employed in a cue-target paradigm. In this task, warning signal words with different hazard levels were used as cues. Participants were required to judge whether targets were presented on the screen horizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…For instance, the communication-human information processing (C-HIP) model of warning signs suggested that there were four stages of information processing before action when people were seeing warning signs. The four stages included attention, comprehension, attitudes and beliefs, and motivation (Wogalter et al, 2005 ; Shang et al, 2015 ). By using Event-Related-Potential (ERP) techniques to study this issue, the researchers found that there were only two stages occurred in brain about dealing with the signal words in safety signs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the communication-human information processing (C-HIP) model of warning signs suggested that there were four stages of information processing before action when people were seeing warning signs. The four stages included attention, comprehension, attitudes and beliefs, and motivation (Wogalter et al, 2005 ; Shang et al, 2015 ). By using Event-Related-Potential (ERP) techniques to study this issue, the researchers found that there were only two stages occurred in brain about dealing with the signal words in safety signs.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the words or phrases depicting such risky events induce more brain activation (a larger central-parietal late positive potential) for processing than that depicting safe events (Qin and Han, 2009 ). Other high-arousal stimuli including warning words (Ma et al, 2010 ; Shang et al, 2015 ), hazardous pictures (Ma et al, 2014 ), and threatening faces (Schupp et al, 2004 ) are relevant to human's safety and thus elicit larger P300. Qin and Han ( 2009 ) suggested that human can extrapolate the severe and dreadful consequence associated with the risky environmental event depicted by words/phrases and retrieve related emotional experience.…”
Section: Discussionmentioning
confidence: 99%
“…Words/phrases, pictures and facial expressions are commonly used as the stimuli to study the emotion processing (Schupp et al, 2004 ; Olofsson et al, 2008 ; Citron, 2012 ). As a powerful communication way, words or phrases are efficient to convey emotion contents and cognitive contents, which are valuable for human's life, for example, alert humans to hazard or risk in a hazardous environment (Qin and Han, 2009 ; Ma et al, 2010 ; Citron, 2012 ; Shang et al, 2015 ). Some words directly express the emotional state (e.g., happy, sad) while others denote the emotional connotation (e.g., reward, danger; Citron, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations